GAMBARAN SANITASI LINGKUNGAN PERUMAHAN GRIYA GURIT PERMAI ROGOJAMPI, KABUPATEN BANYUWANGI - Reza Nabilla Aulyana; Septia Hilda Aisyaroh; Khuliyah Chandraning Diyanah (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Housing is a place to live that cannot be separated and is closely related to economic, industrial and development activities. Housing can be avoided from waste and uninhabitable conditions if housing construction is in accordance with applicable standards, one of which is by implementing healthy housing requirements. The housing problem and the low level of Indonesia are mainly due to poor quality and quantity. The purpose of this study is to describe the description of the physical condition of the house, sanitation, and behavior of the occupants and to describe the residential environment in the Griya Gurit Rogojampi area, Banyuwangi Regency. This research is included in the type of descriptive observational research with a sample of 10 houses. Assessment of the sanitation conditions of houses and housing directly using the instrument. The result of the total score is summed with all the components assessed. The results of the assessment on Griya Gurit Permai Rogojampi Housing, Banyuwangi Regency were included in the good category.